Principal Situational Leadership: A Literature Review - Miftakhul Jannah; Riswanti Rini; Hasan Hariri; Sowiyah Sowiyah (Edumaspul: Jurnal Pendidikan, 2023)
The principal's leadership is related to the leadership style he uses, situational leadership style is one of them. This writer aims to collect and analyze articles related to the situational leadership style of school principals. The method used is literature review articles collected through the Google Scholar search engine and articles that meet the criteria are articles that discuss situational leadership and school principals. Articles that the author selected based on the last 5 years. Based on the articles collected, it was found that the situational leadership of the school principal is an effective and flexible leadership style because the principal is able to adapt to the demands of the existing situation.